Transient ischemic attack and coronary artery disease: a two-sample Mendelian randomization analysis - Qi, Xiaoyi; Wang, Shijia; Qiu, Liangxian; Chen, Xiongbiao; Huang, Qianwen; Ouyang, Kunfu; Chen, Yanjun (Frontiers in Cardiovascular Medicine, 2023)
Background Although observational studies have shown that patients who experienced transient ischemic attacks (TIAs) had a higher risk of coronary artery disease (CAD), the causal relationship is ambiguous. Methods We conducted a two-sample Mendelian randomization (MR) study to analyze the causal relationship between TIA and CAD using data from the FinnGen genome-wide association study. Analysis was performed using the inverse-variance weighted (IVW) method. The robustness of the results was evaluated using MR-Egger regression, the weighted median, MR pleiotropy residual sum, and outlier (MR-PRESSO) and multivariable MR analysis. Results Results from IVW random-effect model showed that TIA was associated with an increased risk of coronary artery atherosclerosis (OR 1.17, 95% CI 1.06–1.28, P = 0.002), ischemic heart disease (OR 1.15, 95% CI 1.04–1.27, P = 0.007), and myocardial infarction (OR1.15, 95% CI 1.02–1.29, P = 0.025). In addition, heterogeneity and horizontal pleiotropy were observed in the ischemic heart disease results, while the sensitivity analysis revealed no evidence of horizontal pleiotropy in other outcomes. Conclusions This MR study demonstrated a potential causal relationship between TIA and CAD. Further research should be conducted to investigate the mechanism underlying the association.